2018
DOI: 10.1002/1873-3468.13291
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic effect of PCPE1 and sFRP2 on the processing of procollagens via BMP1

Abstract: This article corrects: Synergistic effect of PCPE1 and sFRP2 on the processing of procollagens via BMP1, Volume 593, Issue 1, 119–127. Article first published 09 November 2018. https://doi.org/10.1002/1873-3468.13291 Dr Daniel S. Greenspan was inadvertently omitted from the list of authors in the original publication. The correct list of authors is as shown above. Dr Daniel S. Greenspan affiliation and contact details are as follows: Department of Cell and Regenerative Biology, University of Wisconsin, Room 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Binding of the PCPE‐1 NTR domain to BMP‐1 (Fig. ; Bekhouche et al, ) and fibronectin (Weiss et al, ), interaction of fibronectin with syndecans (Xian et al, ), and stimulation by fibronectin of BMP‐1 activity (Huang et al, ) are all consistent with this hypothesis and so are the interaction of PCPE‐1 with fibulin‐4, a protein affecting collagen fibril morphology (Papke et al, ) and the recently demonstrated binding of PCPE‐1 to secreted frizzled‐related protein 2, which results in a synergistic stimulation of procollagen processing by BMP‐1 (Zhu et al, ). The earlier demonstration by Bekhouche et al () that heparan/heparin sulfate increase the enhancing activity of PCPE‐1 in vitro even further (an effect referred to as superstimulation), also supports the above scenario.…”
Section: Discussionmentioning
confidence: 74%
“…Binding of the PCPE‐1 NTR domain to BMP‐1 (Fig. ; Bekhouche et al, ) and fibronectin (Weiss et al, ), interaction of fibronectin with syndecans (Xian et al, ), and stimulation by fibronectin of BMP‐1 activity (Huang et al, ) are all consistent with this hypothesis and so are the interaction of PCPE‐1 with fibulin‐4, a protein affecting collagen fibril morphology (Papke et al, ) and the recently demonstrated binding of PCPE‐1 to secreted frizzled‐related protein 2, which results in a synergistic stimulation of procollagen processing by BMP‐1 (Zhu et al, ). The earlier demonstration by Bekhouche et al () that heparan/heparin sulfate increase the enhancing activity of PCPE‐1 in vitro even further (an effect referred to as superstimulation), also supports the above scenario.…”
Section: Discussionmentioning
confidence: 74%
“…To our knowledge, this was the rst time that PCOLCE was found to be related to ccRCC. PCOLCE is a secreted glycoprotein that participates in the maturation of procollagen and ECM reconstruction by enhancing the activity of bone morphogenetic protein-1 (BMP-1) [24][25][26]. PCOLCE was overexpressed in osteosarcoma, which could promote lung metastasis via twist family bHLH transcription factor 1 (TWIST1).…”
Section: Discussionmentioning
confidence: 99%
“…Collagen formation, assembly and degradation were among the pathways enriched in dermis (Table 1) as a consequence of structural changes by photoageing within the alpha chains of collagens II, IV, VI, XII and XVIII, but also in procollagen C-endopeptidase enhancer-1 (PCOLCE) and cathepsin-B. PCOLCE is crucial for driving the cleavage of type I procollagen by BMP1 during collagen formation (Zhu et al, 2019) whereas cathepsin-B plays an integral role in ECM remodelling, particularly of collagen IV (Buck et al, 1992). In addition, the identified collagen alpha chains interact directly with a range of proteins and glycosaminoglycans (GAGs) (see network: Figure S6).…”
Section: Pathway Analysis Of Skin Proteins With Photoageing-specific ...mentioning
confidence: 99%